Impact of perioperative α1-antagonists on postoperative urinary retention in orthopaedic surgery: meta-analysis. Issue 1 (6th January 2023) - Huang, Yun-Ting; Chang, Yu; Kang, Yi-No; Huang, Chin-Hsuan; Lin, Yu-Shiuan; Wu, Jeffrey; Chi, Kuan-Yu; Chen, Wei-Cheng
Abstract: Background: Postoperative urinary retention (POUR) is a common complication following orthopaedic surgery. Previous studies attempted to establish the preventative role of α1-antagonist in POUR in the general surgical population; however, there is still no consensus regarding its use in orthopaedic surgery due to limited evidence. Methods: Electronic databases of Cochrane Library, Embase, MEDLINE, and ClinicalTrials.gov were searched by two independent investigators from inception to 1 March 2022 to identify relevant randomized clinical trials. Two reviewers independently completed a critical appraisal of included trials by using the Cochrane Risk of Bias tool version 2.0 and extracted data from included articles. Risk of POUR was summarized as risk ratio (RR) with 95 per cent confidence intervals (c.i.). Mean difference (MD) was used for meta-analysis of continuous outcomes. Results: Five randomized clinical trials involving 878 patients (α1-antagonist, 434; placebo, 444) undergoing hip/knee arthroplasty and spine surgeries were included. One study was assessed as high risk of bias from the randomization process and was excluded from the final meta-analysis. There was no difference in the risk of POUR between patients taking α1-antagonist and the placebo in arthroplasty (RR, 0.64; 95 per cent c.i., 0.36 to 1.14) and in spine surgeries (RR, 1.03; 95 per cent c.i., 0.69 to 1.55). There was no difference in length of stay (MD, −0.14 days; 95 per cent c.i., −0.33 to 0.05). Use of α1-antagonist was associated with a higher risk of adverse events (RR, 1.97; 95 per cent c.i., 1.27 to 3.06), with a composite of dizziness, light-headedness, fatigue, altered mental status, and syncope being the most commonly reported symptoms. Conclusion: In patients undergoing spinal surgery and joint arthroplasty, routine administration of perioperative α1-antagonist does not decrease risk of POUR but does increase perioperative dizziness, light-headedness, and syncope. Abstract : In patients undergoing spine surgeries and joint arthroplasty, routine administration of perioperative α1-antagonist does not confer to a decrease in the risk of postoperative urinary retention but a significant increase in the risk of perioperative dizziness, light-headedness, and syncope.